Spherical magnetic flux density sensor array (Transactions on Additive Manufacturing Meets Medicine, 2024)
In the field of medical imaging, particularly magnetic particle imaging, the accurate measurement of magnetic fields in field generators is of significant importance for the assessment of implementation quality and the detection of deviations by the used material and manufacturing tolerances. The data is used to enhance image quality through shimming or physics-informed reconstruction algorithms. However, conventional measurement with a 3-axis Hall probe mounted on a robotic system is time-consuming, presents challenges in terms of reproducibility and is safety-critical due to moving parts. A spherical measuring device is being developed with the objective of enabling fast, accurate and easily reproducible measurements of quasi-static magnetic fields, based on a limited number of support points and field calculations explanting a solid spherical harmonics expansion. A prototype comprising the majority of its electrical and mechanical components through the use of additive manufacturing techniques was developed and produced. The intricate geometry of this design would render conventional manufacturing methods technically very complex and costly. Consequently, additive manufacturing with support material represents an optimal choice for this initial prototype. The results of this prototype serve as a basis for further development, with the aim of developing a user-friendly, stable and modular measuring instrument, with additive manufacturing supporting a fast iterative development.
Keywords: Magnetic Field; magnetic flux density measurement; MPI; Additive Manufacturig; Additive Manufacturing of Electronics